2021
DOI: 10.3390/neurolint13020021
|View full text |Cite
|
Sign up to set email alerts
|

Tinzaparin vs. Nadroparin Safety and Efficacy in Neurosurgery

Abstract: Background. An outbreak of African swine fever (ASF) in China in 2020 has led to an unprecedented shortage of nadroparin. Most patients, especially those kept in hospital for surgery, are currently treated with prophylactic anticoagulation (AC). In search of alternatives for nadroparin (fraxiparine), we found no sufficient data on alternatives for neurosurgical patients, such as tinzaparin of European origin. We compared nadroparin and tinzaparin concerning adverse events (bleeding versus thromboembolic events… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The need for informed consent was waived by the ethics committee of the University of Leipzig. Apart from the patient selection, methodology has been described before 8 , 11 , 12 . I confirm that all methods were performed in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for informed consent was waived by the ethics committee of the University of Leipzig. Apart from the patient selection, methodology has been described before 8 , 11 , 12 . I confirm that all methods were performed in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors for both bleeding and thromboembolic events have been largely examined. To prevent thromboembolism, prophylactic anticoagulation with low molecular weight heparin and its derivatives is standard in perioperative care 6 8 . There are various studies on whether or not to apply chemoprophylaxis or mechanical devices such as intermittent pneumatic compression boots in patients with intracranial pathologies 9 , 10 .…”
mentioning
confidence: 99%
“…A recent pilot study indicates that nadroparin, in comparison with dabigatran or rivaroxaban, showed no difference in bleeding complications in patients with total knee arthroplasty surgery (van der Veen et al, 2021). A retrospective study compared the safety and efficacy of tinzaparin and nadroparin in neurosurgery and showed no significant difference in bleeding events and incidence of VTE (Wilhelmy et al, 2021). Thus, the superiority of tinzaparin and nadroparin in the elderly needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%